The legacy of traditional Indonesian ink: its intensity and durability - Abdul Razak, Rajabi; Barkeshli, Mandana; Othman , Raihan (Eduardo Pulido, 2014)
In Indonesia, the traditional ink also known as mangsi gentur is obtained indigenously by burning kerosene fuel to produce soot. Soot as a carbon source is admixed with sticky rice as a binding agent and then diluted with purified water. The only traditional ink workshop preserving the legacy of this tradition is located in Peuteuy Condong Village, Cianjur, West Java province. The manufacturing process and ink characteristic analysis were carried out in order to examine the ink’s permanency and other properties. This preliminary investigation was conducted using a viscometer, an optical microscope and advanced field emission scanning electron microscopy (FESEM) to identify the ink’s quality as well as its characteristics on two different substrates: Magnani Platinum paper and daluang paper. At constant temperature, the ink is fairly stable and may last for as long as a year without the formation of any insoluble deposit.